Immersive Learning in Higher Education Institutions - Almehrzi, Mouza (2022)
Distance education is one of the techniques that the Ministry of Education provides for students to pursue study, especially in the COVID-19 pandemic. So, the initial experiences of distance education proved several problems, including lack of understanding of the subjects which impact students' performance, lack of collaboration among students, and the massive information students obtain daily. The idea of an immersive learning environment emerged as an educational tool that supports and assists distance learning by using virtual world methods and modern applications to support virtual learning. The study plan of the learners should be modified to align with the Immersive Learning Environment. This research addresses how distance learning and the immersive learning environment affect students' learning, as well as how students benefit from the application of immersive learning in developing the level of academic performance.